Preparation method of nano quartz powder

Through wet grinding process and nano-silicon carbon ore raw materials, combined with grading and filtration technology, nano-quartz powder of 10-30nm was prepared, which solved the problem of difficulty in nano-nanoization and high energy consumption in the existing technology, and achieved high performance and Low-cost quartz powder production.

CN119259210APending Publication Date: 2025-01-07BEIJING YIXING TECH CO LTD +2

Patent Information

Application Number
CN202411433685.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively crush quartz powder to nano-scale particles, resulting in limited application performance in the fields of electronic information, biomedicine, etc., and it is easy to introduce impurities and high energy consumption during the grinding process.

Method used

Wet grinding process combined with micro-nano silicon carbon ore as raw material, nano-quartz powder with particle sizes of 10-30nm is prepared by dispersion, ultrafine grinding, cyclone grading and nano-grinding, combined with nanofiltration grading technology to prevent equipment wear and energy consumption.

Benefits of technology

It achieves high specific surface area and dispersion of quartz powder, reduces particle size, improves application performance, is suitable for large-scale production, is simple in process and low in cost, and is suitable for electronic packaging, special cement and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259210A_ABST
    Figure CN119259210A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of nano quartz powder, which comprises the following steps: S1, based on micro-nano silicon carbon ore as a raw material, adding the raw material into a certain amount of water, and dispersing to form slurry; s2, pumping the slurry into a vertical stirring mill for repeated ultrafine grinding until particles in the slurry reach a first threshold standard, and then forming micron-sized quartz powder slurry; s3, pumping the micron-sized quartz powder slurry into a hydrocyclone for cyclone classification; s4, the overflow slurry obtained through rotational flow classification is pumped into a bead mill to be subjected to repeated nanocrystallization grinding till a second threshold value standard is reached, and therefore a nanocrystallization grinding material is formed; s5, filtering and grading the nanocrystallization grinding material based on a nanofiltration membrane to form dialysate; and S6, drying and scattering the dialysate to obtain the nano quartz powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mineral processing and deep processing methods of non-metallic minerals, and in particular to a method for preparing nano quartz powder. Background Art

[0002] Nano quartz powder has the characteristics of high temperature resistance, small thermal expansion coefficient, high insulation, corrosion resistance, large specific surface area and good reactivity. These characteristics make nano quartz powder play an irreplaceable role in high-end products in the fields of electronic information, biomedicine, special cement, high-end coatings, optical glass, etc.

[0003] Fengcheng Micro-Nano Silicon Carbon Ore benefits from its unique mineralization method. There are a large number of lattice defects inside the quartz grains, which can be crushed and processed into nano-scale particles. Such nano-scale quartz powder has good electrical insulation and has a very low thermal expansion coefficient after melting treatment. It can be used as a packaging filler for high-end integrated circuit products to reduce the thickness of the packaging layer. Nano-quartz powder with high specific surface area can also be used as a filler for high-grade special cement, which can accelerate cement hydration and improve its strength.

[0004] Crushing quartz to nanometer level can significantly improve its application performance. After crushing, the particle size of quartz continues to decrease as the crushing progresses, the specific surface area of ​​quartz will gradually increase, its surface properties will change, and the reactivity of the powder will also be significantly improved. This makes nano quartz powder have higher and better performance than simply crushed quartz powder in application.

[0005] The dry processes currently used for quartz grinding mainly include Raymond mill (roller mill), vertical mill or airflow mill grinding. Because of the high hardness of quartz, most of these production processes can only crush quartz to the micron level, and the wear of the equipment during the process will also introduce a considerable amount of impurities, which will affect the use effect of quartz powder. The wet grinding process includes sand mill, vertical ball mill, and planetary high-energy ball mill grinding. Because the surface energy increases due to the reduction of quartz powder particle size, the agglomeration phenomenon is very serious during the actual grinding process, and nano-grinding is very difficult. In addition, the existing methods are used to destroy the crystal structure of quartz at the nanoscale. The particle size of the quartz powder after grinding is subject to the grain size, generally at the micron level. Even if Fengcheng micro-nano silicon carbon ore is used as the raw material, the particle size of the quartz powder obtained by the grinding method alone is above 50nm. Summary of the invention

[0006] In order to solve the technical defects and deficiencies in the prior art, the present invention provides the following technical solutions: a method for preparing nano quartz powder, using a wet grinding process to prepare nano quartz powder, which can greatly increase the specific surface area of ​​quartz powder and reduce its particle size, and innovatively use nano silicon carbon ore as a raw material, using its mineral structure characteristics to achieve the preparation of nano quartz powder, using micro-nano silicon carbon ore to prepare nano quartz powder with a particle size of 10 to 30 nm and a high specific surface area, improving the application performance and use value of micro-nano silicon carbon ore, avoiding the energy consumed by the equipment to break quartz grains and form defects during the grinding process, and at the same time, the nano quartz powder obtained by grinding is graded by a cross-flow filtration method, avoiding the energy consumption problem caused by long-term grinding. The process of the present invention is more environmentally friendly than chemically synthesized quartz powder, and is suitable for large-scale production, simple in process, low in cost, and fine in product particle size, and the particle size of the obtained quartz powder is between 10 and 30 nm. While preparing nano quartz powder, it also has excellent dispersibility, which makes the quartz powder have more superior application performance in the fields of electronic packaging, high-end coatings, special cement, high-end resins and fine polishing, which is of great significance to the quartz industry chain.

[0007] The present invention provides a method for preparing nano quartz powder, comprising the following steps:

[0008] S1, based on micro-nano silicon carbon ore as raw material, is added into a certain amount of water for dispersion to form a slurry;

[0009] S2, pumping the slurry into a vertical stirred mill for repeated ultrafine grinding until the particles in the slurry reach a first threshold standard to form a micron-sized quartz powder slurry;

[0010] S3, pumping the micron-sized quartz powder slurry into a hydrocyclone for cyclone classification;

[0011] S4, pumping the overflow slurry obtained by the cyclone classification into a bead mill for repeated nano-grinding until it reaches a second threshold standard, thereby forming a nano-grinding material;

[0012] S5, filtering and grading the nano-ground material through a nanofiltration membrane to form a dialysate;

[0013] S6, drying and breaking up the dialysate to obtain nano-quartz powder.

[0014] Preferably, the S1 comprises:

[0015] S11, preparing micro-nano silicon-carbon ore as a raw material, and adding a certain amount of water to the raw material to form a first mixture; wherein the size requirement of the micro-nano silicon-carbon ore is that particles smaller than 74 microns account for more than 95%.

[0016] S12, adding an appropriate amount of grinding aid to the first mixture;

[0017] S13, breaking up the first time length in a high-speed stirring disperser to form a slurry.

[0018] Preferably, the grinding aid is a silane coupling agent, triethanolamine or sodium hexametaphosphate.

[0019] Preferably, the first duration is 0.5h-4h.

[0020] Preferably, the mass ratio of the micro-nano silicon carbon ore, water and grinding aid is: 100: (100-1000): (0.5-5).

[0021] Preferably, the ultrafine grinding uses alumina ceramic beads or zirconia ceramic beads as grinding media; the size of the grinding media is Φ0.5mm-5mm; and the filling rate of the grinding media in the grinding cavity is 55%-80%.

[0022] Preferably, the size of the hydrocyclone is Φ10mm-100mm, and the cyclone pressure of the cyclone classification is 0.1Mpa-1.5Mpa.

[0023] Preferably, the nano-grinding uses alumina ceramic beads or zirconia ceramic beads as grinding media, the size of the grinding media is Φ0.03mm-0.5mm, and the filling rate of the grinding media in the grinding cavity is 65%-80%.

[0024] Preferably, the first threshold standard is that 70% of the particles by mass in the slurry after the ultrafine grinding have a particle size less than 2 microns; the second threshold standard is that 90% of the particles by mass in the nano-ground material have a particle size less than 100 nanometers.

[0025] Preferably, the molecular weight cutoff of the nanofiltration membrane is 100k to 500k Daltons; the type of the nanofiltration membrane is a hollow fiber membrane or a spiral membrane.

[0026] Beneficial effects of the present invention:

[0027] (1) Innovatively use micro-nano silicon carbon ore as raw material to prepare nano quartz powder. The quartz powder has excellent dispersibility, which solves the grinding resistance problem caused by complete quartz grains during the grinding process;

[0028] (2) The cyclone classification process is innovatively used to separate biogenic quartz powder from non-biogenic quartz powder. At the same time, nanofiltration classification technology is used to separate the quartz powder with the smallest particle size after nano-grinding, thereby reducing the energy loss caused by agglomeration during the grinding process and achieving the purpose of preparing nano-quartz powder.

[0029] (3) Compared with the general wet grinding process and dry process (air flow mill, roller mill) of quartz ore, it has the advantages of fine product particle size (10-30nm), low energy consumption, low cost, environmentally friendly process, easy industrialization, etc., and can ensure the purity of quartz powder. It can have good performance in application scenarios such as electronic packaging, special cement, high-end coatings, 3D printing fillers, etc.

[0030] (4) The processing method has a simple process flow. Nano-quartz powder slurry with a particle size of 10 to 30 nm can be obtained by breaking up, ultrafine grinding, cyclone, nano-grinding and nanofiltration classification. Subsequently, drying and breaking up can be performed to obtain nano-quartz powder with a particle size of 10 to 30 nm and a particle content of more than 90%. It has the advantages of simple processing technology, low energy consumption, low cost and easy industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention provides a flow chart of the method for preparing nano-quartz powder.

[0032] Figure 2 The present invention provides a process flow chart of using micro-nano silicon carbon ore as raw material, adding it into a certain amount of water for dispersion to form a slurry.

[0033] Figure 3 The present invention provides a scanning electron microscope image of the prepared nano-quartz powder with a scale of 100,000.

[0034] Figure 4 The scanning electron microscope image of the prepared nano-quartz powder provided by the present invention has a scale of 65000.

[0035] Figure 5 The present invention provides a scanning electron microscope image of the prepared nano-quartz powder with a scale of 50,000.

[0036] Figure 6 Schematic diagram of the decomposition process of the new mineral sample provided by the present invention.

[0037] Figure 7 Schematic diagram of X-ray diffraction analysis (XRD) of the new mineral provided by the present invention.

[0038] Figure 8 This is a scanning electron microscope image of the mineral sample provided by the present invention and a schematic diagram of the specific surface area and pore analysis results. DETAILED DESCRIPTION

[0039] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0040] like Figure 1As shown, an embodiment of the present invention provides a method for preparing nano-quartz powder, comprising the following steps:

[0041] S1, based on micro-nano silicon carbon ore as raw material, is added into a certain amount of water for dispersion to form a slurry;

[0042] like Figure 2 As shown, as a preferred embodiment, the S1 includes:

[0043] S11, preparing micro-nano silicon carbon ore as a raw material, and adding a certain amount of water to the raw material to form a first mixture;

[0044] As a preferred embodiment, the size requirement of the micro-nano silicon carbon ore is that particles smaller than 74 microns account for more than 95% (d 95 <74μm).

[0045] S12, adding an appropriate amount of grinding aid to the first mixture;

[0046] As a preferred embodiment, the grinding aid is a silane coupling agent, triethanolamine or sodium hexametaphosphate.

[0047] S13, breaking up the first time length in a high-speed stirring disperser to form a slurry.

[0048] As a preferred implementation, the first duration is 0.5h-4h.

[0049] As a preferred embodiment, the mass ratio of the micro-nano silicon carbon ore, water and grinding aid is: 100: (100-1000): (0.5-5).

[0050] As a preferred embodiment, when the grinding aid is a silane coupling agent, the mass ratio of the micro-nano silicon carbon ore, water and the grinding aid is: 100: (200-400): (1.5-2), and the first time length is 0.5h-2h.

[0051] S2, pumping the slurry into a vertical stirred mill for repeated ultrafine grinding until the particles in the slurry reach a first threshold standard to form a micron-sized quartz powder slurry;

[0052] As a preferred embodiment, the ultrafine grinding uses alumina ceramic beads or zirconia ceramic beads as grinding media; the size of the grinding media is Φ0.5mm-5mm; and the filling rate of the grinding media in the grinding cavity is 55%-80%.

[0053] As a preferred embodiment, when the grinding media used are zirconia ceramic beads, the size of the zirconia ceramic beads is Φ1 mm to 3 mm, and the filling rate of the zirconia ceramic beads in the grinding cavity is 70% to 80%.

[0054] As a preferred embodiment, the first threshold standard is that the particle size of 70% of the mass fraction of the particles in the ultrafine grinding slurry is less than 2 microns (d 70 <2μm).

[0055] S3, pumping the micron-sized quartz powder slurry into a hydrocyclone for cyclone classification;

[0056] As a preferred embodiment, the size of the hydrocyclone is Φ10mm-100mm, and the cyclone pressure of the cyclone classification is 0.1Mpa-1.5Mpa.

[0057] As a more preferred embodiment, the size of the hydrocyclone is Φ10mm-25mm, and the cyclone pressure of the cyclone classification is 0.4Mpa-0.8Mpa.

[0058] S4, pumping the overflow slurry obtained by the cyclone classification into a bead mill for repeated nano-grinding until a second threshold standard is reached, thereby forming a nano-grinding material.

[0059] As a preferred embodiment, the nano-grinding uses alumina ceramic beads or zirconia ceramic beads as grinding media, the size of the grinding media is Φ0.03mm-0.5mm, and the filling rate of the grinding media in the grinding cavity is 65%-80%.

[0060] As a more preferred embodiment, the size of the grinding medium is Φ0.03 mm to 0.1 mm, and the filling rate of the grinding medium in the grinding chamber is 70% to 80%.

[0061] As a preferred embodiment, the second threshold standard is that 90% of the particles in the nano-grinding material have a particle size less than 100 nanometers (d 90 <100nm);

[0062] S5, filtering and grading the nano-ground material through a nanofiltration membrane to form a dialysate;

[0063] As a preferred embodiment, the molecular weight cutoff of the nanofiltration membrane is 100k to 500k Daltons; the type of the nanofiltration membrane is a hollow fiber membrane or a spiral membrane.

[0064] As a more preferred embodiment, the molecular weight cutoff of the nanofiltration membrane is 100k to 300k Daltons, and the type of the nanofiltration membrane is a spiral membrane.

[0065] S6, drying and breaking up the dialysate to obtain nano-quartz powder.

[0066] As a preferred embodiment, the particle size of the nano-quartz powder is between 10 and 30 nm.

[0067] Figure 3 The scanning electron microscope image of the prepared nano-quartz powder is at a scale of 100,000; Figure 4 The scanning electron microscope image of the prepared nano-quartz powder is at a scale of 65000; Figure 5 The scanning electron microscope image of the prepared nano-quartz powder is at a scale of 50000. As can be seen from the scale, the particle size of the particles in the image is about 10-20nm.

[0068] The novel mineral used in the following examples is taken from Fengcheng City, Jiangxi Province, and is black in color. The composition research method and specific process are as follows.

[0069] 1. Thermal Analysis

[0070] like Figure 6 As shown in the figure, the atmosphere for thermal analysis of the sample is air, and a Pt crucible is used as a sample stage to load the sample. Under the condition of a heating rate of 10℃ / min, the TG, DTG and DSC curves of the sample are obtained, proving that the mineral has two main decomposition stages during the heating process to 1000℃. The first stage of sample decomposition is at 25℃~200℃, which is manifested as a convexity on the DSC curve and is an endothermic reaction. This stage involves two processes: the volatilization of a small amount of water in the sample and the dehydroxylation of the sample. Through image data analysis, it can be seen that the mass percentage of water and hydroxyl contained in the sample is 1.05%. The second stage of sample decomposition is 420℃~720℃, which is manifested as a depression on the DSC curve and is an exothermic reaction, mainly related to the oxidation and combustion of carbon in the sample. From the DSC curve, it can be seen that the peak value of the exothermic peak in this stage is 625.9℃, that is, the oxidation rate of carbon in the sample is the largest at this temperature, and its heat release can reach 7.531mW / mg. At the same time, the DTG curve shows that at 620.7°C, the mass percentage change rate of the sample reaches the fastest, which is -2.17% / min. The ignition loss ratio calculated by the TG curve shows that the mass percentage loss of the sample at this stage is 20.34%, that is, the sample contains a corresponding proportion of elemental carbon.

[0071] 2. X-ray diffraction analysis

[0072] like Figure 7 As shown, X-ray diffraction analysis (XRD) is mainly aimed at the analysis of crystalline substances in minerals. By analyzing the diffraction peaks of the XRD spectrum, the components of the crystalline substances in the minerals and the content of each component can be obtained. The embodiment of the present invention performs an X-ray diffraction scan of the mineral sample with a 2θ of 10-80 degrees, and it can be determined that the crystalline substances in the minerals include quartz, kaolinite, gypsum and pyrite.

[0073] Through further analysis of the XRD pattern, the Miller indices can be marked according to the diffraction peaks in the figure as (001), (100), (101), (200), (004), (104), (213), (204), (312), (223), (204), (223),

[0074] (202), (311), (314), (321), (206) crystal planes. After comparison with the open database, it can be determined that the components are quartz, pyrite, kaolinite and mica. The content of each component can be calculated by analyzing the intensity of the diffraction peaks. The mass fractions of each component are shown in Table 1.

[0075] Table 1 Composition and mass fraction of crystalline substances in new minerals

[0076] Components quartz Pyrite Kaolinite Mica Quality score 91% 4% 4% 1%

[0077] It can be seen that the crystalline component of the mineral is mainly quartz, containing a small amount of pyrite, kaolinite and mica as impurities.

[0078] 3. Microscopic Analysis

[0079] Microscopic analysis mainly uses scanning electron microscopy (SEM) and X-ray energy dispersive spectroscopy (EDS) to test the structure and element distribution of samples. The test samples are raw minerals and processed mineral samples. The mineral processing methods include ultrasonic cleaning, high-temperature carbon removal, chemical carbon removal, and chemical silicon dioxide removal. By observing the above five test samples, the microscopic composition of the minerals can be comprehensively analyzed and the suitability of the corresponding processing methods can be explored.

[0080] First, the morphology of the original ore was observed using SEM, and its element content was analyzed using EDS. In order to observe the mineral without destroying the basic structure of the mineral, the original mineral was dispersed in alcohol, shaken briefly, and then dropped on aluminum foil to make a scanning electron microscope sample for observation. The mineral is composed of multiple fragments stacked together, with a large number of gaps and holes. There are circular depressions and strip-shaped scratches on the surface of these block structures, which may be caused by biological etching. In addition to the block structure, there are a large number of rods on the surface of the mineral, with a diameter of 50-100nm and a length of 500nm-1μm.

[0081] Further EDS spectrum analysis of some areas shows that the main elements in the mineral are C, O, Al and Si, among which C has the highest content, accounting for 42.51% by mass, and Al has the lowest content, accounting for 4.64% by mass.

[0082] Combined with the results of thermal analysis and XRD, the mass percentage of C element obtained by EDS energy spectrum scanning is much higher than 20.34%, which shows that carbon element is mainly enriched on the surface of the mineral or in some special structures, rather than uniformly distributed in the mineral structure. Carbon and quartz grow together, and silicon dioxide can be obtained by removing carbon.

[0083] like Figure 8 The scanning electron microscope image of the mineral sample shown and the schematic diagram of the specific surface area and pore analysis results. In order to observe the inner structure of the mineral more carefully and clearly, the present invention uses an ultrasonic cleaning method to separate the debris and impurities on the surface of the mineral particles. The mineral sample is dispersed in alcohol, ultrasonically cleaned for 15 minutes, and dropped on a silicon wafer to prepare a scanning electron microscope sample for observation. The obtained scanning electron microscope image shows that the debris and rods on the mineral surface are basically eliminated after ultrasonic cleaning, which also shows that ultrasonic cleaning can effectively separate the debris and impurities on the mineral surface. There are circular depressions of different sizes on the mineral particles, and there are mesoporous and microporous structures. There are circular depressions on the mineral particles, and there are notches and cracks.

[0084] 4. Specific surface area and pore analysis

[0085] Specific surface area and pore analysis mainly uses specific surface area and pore analyzers to detect the specific surface area and pore structure of the sample. The algorithm used for the detection is mainly BET. The test sample is a mineral sample. After the sample is dried at 115°C, nitrogen is used as the adsorbent for BET specific surface area test.

[0086] The BET specific surface area of ​​the original mineral sample obtained by testing is 5.2684m2 / g, the total pore volume is 0.028110cm3 / g, the average adsorption pore diameter is 213.421 angstroms, and the average desorption pore diameter is 201.633 angstroms.

[0087] In summary, the new mineral of the present invention includes crystalline components and amorphous components, wherein the crystalline components account for 78.61% of the mineral mass fraction, and the amorphous components account for 21.39% of the mineral mass fraction; wherein the crystalline components are quartz, pyrite, kaolinite and mica, and the mass fraction of quartz in the crystalline group is 91%, and the amorphous substances are water, elemental carbon and organic matter, and the carbon content is 20.34%.

[0088] Example 1

[0089] This embodiment provides a method for preparing nano-quartz powder, comprising the following steps:

[0090] 1) Fengcheng micro-nano silicon carbon ore (quartz particle size distribution d 90=64.58μm), add to a certain amount of water, and add silane as a grinding aid, the ratio is: Fengcheng micro-nano silicon carbon ore: water: silane = 100:150:1. Disperse in a high-speed stirring disperser for 4h.

[0091] 2) Add Φ1mm zirconium oxide ceramic beads into the vertical stirred mill with a filling rate of 75%. Then pump the material into the mill and grind it repeatedly. After grinding for 8 times, pump it out to obtain sample slurry d 70 =1.81μm.

[0092] 3) The product obtained in step 2) was pumped into a Φ25 mm hydrocyclone for cyclone classification at a cyclone pressure of 0.6 MPa. Overflow slurry d was obtained. 90 =2.15μm

[0093] 4) The overflow slurry in 3) is pumped into a bead mill for nano-grinding. Zirconia with a diameter of 0.05 mm is used as the grinding medium. The filling rate of diamond in the machine is 65%.

[0094] 5) The material was repeatedly ground in a bead mill for 30 times to obtain slurry d 90 =0.09 μm, and then filtered using a spiral membrane with a molecular weight cutoff of 100k Dalton to obtain a dialysate slurry.

[0095] 6) Dry and break up the dialysate slurry to obtain 90 =14nm nano quartz powder.

[0096] Example 2

[0097] This embodiment provides a method for preparing nano-quartz powder, comprising the following steps:

[0098] 1) Fengcheng micro-nano silicon carbon ore (quartz particle size distribution d 90 =45.69μm), add to a certain amount of water, and add triethanolamine as a grinding aid, the ratio is: Fengcheng micro-nano silicon carbon ore: water: triethanolamine = 100:200:1. Disperse in a high-speed stirring disperser for 3h.

[0099] 2) Add Φ0.8mm zirconium oxide ceramic beads into the vertical stirred mill with a filling rate of 80%. Then pump the material into the mill and grind it repeatedly. After grinding for 6 times, pump it out to obtain sample slurry d 70 =1.75μm.

[0100] 3) The product obtained in step 2) was pumped into a Φ10 mm hydrocyclone for cyclone classification at a cyclone pressure of 0.4 MPa. Overflow slurry d was obtained. 90 =2.21μm

[0101] 4) The overflow slurry in 3) is pumped into a bead mill for nano-grinding. Zirconia with a diameter of 0.04 mm is used as the grinding medium. The filling rate of diamond in the machine is 70%.

[0102] 5) The material was repeatedly ground in a bead mill for 30 times to obtain slurry d 90 =0.07 nm, and then filtered using a hollow fiber membrane with a molecular weight cutoff of 500k Dalton to obtain a dialysate slurry.

[0103] 6) Dry and break up the dialysate slurry to obtain 90 =28nm nano quartz powder.

[0104] Example 3

[0105] This embodiment provides a method for preparing nano-quartz powder, comprising the following steps:

[0106] 1) Fengcheng micro-nano silicon carbon ore (quartz particle size distribution d 90 =71.75μm), add to a certain amount of water, and add sodium hexametaphosphate as a grinding aid, the ratio is: Fengcheng micro-nano silicon carbon ore: water: sodium hexametaphosphate = 100:200:2.5. Disperse in a high-speed stirring disperser for 3.5h.

[0107] 2) Add Φ0.5mm alumina ceramic beads into the vertical stirred mill with a filling rate of 55%. Then pump the material into the mill and grind it repeatedly. After grinding for 6 times, pump it out to obtain sample slurry d 70 =1.70μm.

[0108] 3) The product obtained in step 2) was pumped into a Φ10 mm hydrocyclone for cyclone classification at a cyclone pressure of 0.3 MPa. Overflow slurry d was obtained. 90 =1.95μm

[0109] 4) The overflow slurry in 3) is pumped into a bead mill for nano-grinding. Alumina with a diameter of 0.1 mm is used as the grinding medium. The filling rate of diamond in the machine is 65%.

[0110] 5) The material was repeatedly ground in a bead mill for 30 times to obtain slurry d 90 =0.07 nm, and then filtered using a spiral membrane with a molecular weight cutoff of 250k Dalton to obtain a dialysate slurry.

[0111] 6) Dry and break up the dialysate slurry to obtain 90 =21nm nano quartz powder.

[0112] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing nano quartz powder, characterized in that: The steps include: S1, based on micro-nano silicon carbon ore as raw material, is added into a certain amount of water for dispersion to form a slurry; S2, pumping the slurry into a vertical stirred mill for repeated ultrafine grinding until the particles in the slurry reach a first threshold standard to form a micron-sized quartz powder slurry; S3, pumping the micron-sized quartz powder slurry into a hydrocyclone for cyclone classification; S4, pumping the overflow slurry obtained by the cyclone classification into a bead mill for repeated nano-grinding until it reaches a second threshold standard, thereby forming a nano-grinding material; S5, filtering and grading the nano-ground material through a nanofiltration membrane to form a dialysate; S6, drying and breaking up the dialysate to obtain nano-quartz powder.

2. The method for preparing nano quartz powder according to claim 1, characterized in that: The S1 includes: S11, preparing micro-nano silicon-carbon ore as a raw material, and adding a certain amount of water to the raw material to form a first mixture; wherein the size requirement of the micro-nano silicon-carbon ore is that particles smaller than 74 microns account for more than 95%. S12, adding an appropriate amount of grinding aid to the first mixture; S13, breaking up the first time length in a high-speed stirring disperser to form a slurry.

3. The method for preparing nano quartz powder according to claim 2, characterized in that: The grinding aid is a silane coupling agent, triethanolamine or sodium hexametaphosphate.

4. The method for preparing nano quartz powder according to claim 3, characterized in that: The first duration is 0.5h-4h.

5. The method for preparing nano quartz powder according to claim 4, characterized in that: The mass ratio of the micro-nano silicon carbon ore, water and grinding aid is: 100: (100-1000): (0.5-5).

6. The method for preparing nano quartz powder according to claim 5, characterized in that: The ultrafine grinding uses alumina ceramic beads or zirconia ceramic beads as grinding media; the size of the grinding media is Φ0.5mm-5mm; the filling rate of the grinding media in the grinding cavity is 55%-80%.

7. The method for preparing nano quartz powder according to claim 6, characterized in that: The size of the hydrocyclone is Φ10mm-100mm, and the cyclone pressure of the cyclone classification is 0.1Mpa-1.5Mpa.

8. The method for preparing nano quartz powder according to claim 7, characterized in that: The nano-grinding uses alumina ceramic beads or zirconia ceramic beads as grinding media, the size of the grinding media is Φ0.03mm-0.5mm, and the filling rate of the grinding media in the grinding cavity is 65%-80%.

9. The method for preparing nano quartz powder according to claim 8, characterized in that: The first threshold standard is that 70% of the particles by mass in the ultrafine grinding slurry have a particle size less than 2 microns; the second threshold standard is that 90% of the particles by mass in the nano-grinding material have a particle size less than 100 nanometers.

10. The method for preparing nano quartz powder according to claim 9, characterized in that: The molecular weight cutoff of the nanofiltration membrane is 100k-500k Daltons; the type of the nanofiltration membrane is a hollow fiber membrane or a rolled membrane.

Citation Information

Patent Citations

  • Method for preparing nanometer silica micropowder

    CN101659393A

  • Method for purifying powdery quartz

    CN102039217A

  • Method for preparing natural mica powder

    CN105731472A

  • Preparation method for nanometer tourmalinite powder

    CN107096610A

  • Nano talcum powder and preparation method thereof

    CN116462994A

Cited By

  • Low-conductivity superfine silica powder as well as preparation method and application thereof

    CN120247042A